State Responsibility in Protecting Human Rights: An International Legal Perspective - Hidayah, Syarifaatul (International Law Discourse in Southeast Asia, 2023)
The protection of human rights is a cornerstone of international law, with states bearing primary responsibility for ensuring the rights and freedoms of individuals within their jurisdiction. This study provides an in-depth analysis of state responsibility in safeguarding human rights from an international legal perspective. Beginning with an exploration of the foundational principles enshrined in international human rights instruments and customary international law, the study examines the legal obligations incumbent upon states in upholding human rights standards. Key components of state responsibility in protecting human rights are delineated, including the duty to respect, protect, and fulfill human rights, as well as the obligation to prevent and remedy human rights violations. Through a comprehensive review of relevant case law, treaties, and legal scholarship, the study elucidates the evolving nature of state responsibility and the mechanisms available for holding states accountable for human rights abuses. Furthermore, the study explores the role of international institutions, such as regional human rights bodies and the International Criminal Court, in adjudicating human rights violations and enforcing state compliance with international legal standards. Special attention is given to the intersection of state sovereignty and human rights protection, examining the balance between state autonomy and international intervention in cases of egregious human rights violations. In conclusion, the study underscores the indispensable role of states in fulfilling their duty to protect human rights, emphasizing the importance of effective domestic legislation, institutional mechanisms, and accountability measures. By elucidating the legal framework governing state responsibility in human rights protection, this analysis aims to contribute to the advancement of human rights norms and the promotion of global justice and dignity for all individuals.